Pelatihan Foto Produk Usaha Mikro, Kecil dan Menengah Nizam Jaya - Ihtadat Alam Makarima Mainun; Lia Nirawati (Yayasan Daarul Huda Kruengmane, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are one of the factors driving economic development in Indonesia. The fact that internet development has reached a very fundamental human need enables MSMEs to expand their businesses worldwide. They are, of course, required to understand some basic skills and competencies to survive in the online business, such as electronic market share, e-market ethics, and e-market advertising. The core subjects of e-market advertising are product photography and product design. As smartphones have significantly advanced nowadays, all the mentioned processes can be conducted through them. This training is specifically designed for this purpose, which is to develop the skills of MSME communities in smartphone product photography and packaging techniques so that they can compete and succeed in the electronic market. The training has been quite successful, as evidenced by the enthusiasm of the participants and the production of some excellent product photographs. The result of this training is the increasing number of MSME practitioners going online and promoting their products on the internet.